Effects of Robot-Assisted Therapy on Gait Parameters in Pediatric Patients With Spastic Cerebral Palsy - Manikowska, Faustyna; Brazevic, Sabina; Krzyżańska, Anna; Jóźwiak, Marek (Frontiers in Neurology, 2021)
Background: Gait dysfunction is a crucial factor that restricts independence and quality of life in children with cerebral palsy (CP). Gait training based on robotic-assisted therapy (RAT) is widely used, but information about effectiveness and ideal patient profile is not sufficient. Aim of the study was to assess the effect of RAT on gait parameters in spastic children with CP and to determine whether changes in gait parameters are different among patients on different ambulatory levels. Method: Twenty-six children with bilateral spastic CP were divided into 2 groups based on their functional ability: non-assisted ambulator (NAS) or assisted ambulator (AS); and underwent a RAT program (30 training sessions of RAT during 10 weeks). Gait analysis was performed: before the therapy (t1), right after (t2), and 6 weeks later (t3). Results: No significant changes in spatiotemporal parameters or Gait Deviation Index at t2 or t3. Double support symmetry significantly improved (t1 vs t3, p=0.03) for the whole group (NAS+AS). Walking speed symmetry significantly improved (t2 vs t3, p=0.02) for group AS. Conclusion: RAT based on our protocol, didn’t change spatiotemporal parameters and kinematics of walking except limited improvement in some aspects of gait symmetry. We didn’t find differences in changes in selected objective gait parameters among children with CP in different ambulatory levels.